PENGEMBANGAN LKPD BERBASIS PBL BERBANTUAN PHET SIMULATION UNTUK MENINGKATKAN KEMAMPUAN LITERASI SAINS PESERTA DIDIK PADA MATERI GELOMBANG CAHAYA - Leni; Widodo (JPFT (Jurnal Pendidikan Fisika Tadulako Online), 2021)
The purpose of this research is to find out the eligibility and the use practicality of LKPD based on PBL assisted by phet simulation to improve the scientific literacy ability on light wave. There are two LKPD that developed. LKPD 1 is interference and LKPD 2 is polarization, both of them are sub-materials of light waves. Method that being used in this research is Educational Research Development (R&D) that modified by Borg & Gall (1983). This research is limited to five steps, 1) preliminary research, 2) Product Design, 3) Product Validation, 4) Product Revision, and 5) Evaluation/ Main field testing. From the results of the study, it was found that the LKPD based on PBL assisted by phet simulation to improve the scientific literacy ability on light wave is applicable to be used as a learning media because theoretically meet the eligibility requirements with an average percentage of 94% in LKPD 1 and 95% in LKPD 2.  In the practicality test, it was found that the PBL-based LKPD assisted by phet simulation was very practical for students to be used with the average percentage of response results being 84% for the LKPD 1 and 85% for the LKPD 2.